Real-world implementation of sequential targeted therapies for EGFR-mutated lung cancer - Magios, Nikolaus; Bozorgmehr, Farastuk; Volckmar, Anna-Lena; Kazdal, Daniel; Kirchner, Martina; Herth, Felix; Heußel, Claus Peter; Eichhorn, Florian; Meister, Michael; Muley, Thomas; El-Shafie, Rami; Fischer, Jürgen; et al. (Therapeutic advances in medical oncology, 2021)
Background:Epidermal growth factor receptor-mutated (EGFR+) non-small-cell lung cancer (NSCLC) patients failing tyrosine kinase inhibitors (TKI) can benefit from next-line targeted therapies, but implementation is challenging.Methods:EGFR+ NSCLC patients treated with first/second-generation (1G/2G) TKI at our institution with a last follow-up after osimertinib approval (February 2016), were analyzed retrospectively, and the results compared with published data under osimertinib.Results:A total of 207 patients received erlotinib (37%), gefitinib (16%) or afatinib (47%). The median age was 66?years, with a predominance of female (70%), never/light-smokers (69%). T790M testing was performed in 174/202 progressive cases (86%), positive in 93/174 (53%), and followed by osimertinib in 87/93 (94%). Among the 135 deceased patients, 94 (70%) received subsequent systemic treatment (43% chemotherapy, 39% osimertinib), while 30% died without, either before (4%) or after progression, due to rapid clinical deterioration (22%), patient refusal of further therapy (2%), or severe competing illness (2%). Lack of subsequent treatment was significantly (4.5x, p?